Where is 'East of Eden'?: The Politics of Steinbeck's Literary Reputation in Slovenia - Čerče, Danica (Archīum Ateneo, 2024)
Katherine Arens maintains that literary texts or authors can function as prototypes for their speech genres within literary history and in a cultural community. Until very recently, in Slovenia, John Steinbeck has been regarded primarily as an objective social chronicler of the Great Depression. This popular critical view, earned with his “labor trilogy,” The Grapes of Wrath, In Dubious Battle, and Of Mice and Men, is needlessly limiting, given that Steinbeck’s literary achivements extend well beyond the modes and methods of traditional realism or documentary representation. Written against the background of the critical discourse regarding the political implications of literary works and the ways in which readers are involved in creating the texts they read, this essay analyzes the indicators of and the plausible reasons for the unprecedented popularity of Steinbeck’s novel East of Eden. It shows that in past decades, when Slovenia was in the grip of communist rule, even this book, concerned with moral dilemmas and personal traumas, rather than dealing with the workers’ struggle for social change, could not escape a political reading and served to promote an ideology it does not formally articulate.